Tranexamic Acid and the Risk of Delirium after Off-Pump Surgery - Hulde, Nikolai; Zittermann, Armin; Deutsch, Marcus-Andre; Gummert, Jan F.; von Dossow, Vera; Koster, Andreas (The Thoracic and Cardiovascular Surgeon, 2022)
We investigated whether in patients undergoing off-pump coronary artery bypass grafting surgery a single bolus of 1 g tranexamic acid (TXA) impacts the risk of postoperative delirium using the propensity score matching approach. In 2,757 pairs, the risk of delirium was 4.2% (TXA group) and 5.0% (non-TXA group), with a relative risk in the TXA versus the non-TXA group of 0.83 (95% confidence interval: 0.65–1.07; p = 0.16). There was no significant interaction between TXA administration and renal function on the risk of delirium (p = 0.12). Data indicate that a single bolus of 1 g TXA does not increase the risk of delirium in patients undergoing off-pump surgery.
Keywords: delirium; tranexamic acid; renal impairment